Detection of brain tumour using segmentation - V.Prakash, V; Manjunathachari, K (International Journal of Engineering and Technology, 2018)
This paper presents the detection of the brain tumour by improvised image segmentation technique. The Magnetic Resonance Image is considered for the purpose of detecting the brain tumour. The human brain occupies 2% of the body’s weight. The Magnetic Resonance Image is preferred over the CT scan image for accuracy of the MRI based brain tumour detection is high. Though there are several techniques of segmentations, the water shed proves to be advantages in detecting the region of interest. The score plot of the vertical and horizontal plane exhibits high efficiency and feasibility of the technique presented.